2014
DOI: 10.1016/j.crm.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing data for managing climate risks: Index-based insurance and growth related applications for smallhold-farmers in Ethiopia

Abstract: a b s t r a c tThe aim of most index-based insurance programs is to act as a social security mechanism and to provide defense against social and financial exclusion for people whose existing coping strategies are failing. For such schemes, insurance payouts do not depend on the individual losses but on an index which serves as a proxy for the losses. As proposed in this paper, also remote sensing data can be used for index-based insurance which gives additional advantages in comparison to traditional on-ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…In addition to the frequency of payouts, their timing also matters. Optimising remote sensing data for instance and providing earlier payouts could allow vulnerable farmers to utilise mitigation strategies such as alternative forage sources for livestock (Vrieling et al, 2016) or access to food to prevent farmers from falling below the minimum food requirements (Hochrainer-Stigler et al, 2014). Vrieling et al (2016) showed that payouts made between one to three months before the onset of the drought would give farmers more time to optimise protective alternatives.…”
Section: Trigger Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the frequency of payouts, their timing also matters. Optimising remote sensing data for instance and providing earlier payouts could allow vulnerable farmers to utilise mitigation strategies such as alternative forage sources for livestock (Vrieling et al, 2016) or access to food to prevent farmers from falling below the minimum food requirements (Hochrainer-Stigler et al, 2014). Vrieling et al (2016) showed that payouts made between one to three months before the onset of the drought would give farmers more time to optimise protective alternatives.…”
Section: Trigger Periodmentioning
confidence: 99%
“…To capture the entirety of insured peril basis risk, insurance product development might consider using multiple sources and types of data to better explain both the production risk and multiple dimensions of possible losses (Wang et al, 2013). While indices have always been constructed by single variables such as remotely sensed vegetation or rainfall or temperature data (Hochrainer-Stigler et al, 2014;Vrieling et al, 2014;De Oto et al, 2019), more recently, new variables such as soil moisture have shown promise in indices (Enenkel et al, 2017(Enenkel et al, , 2019Von Negenborn et al, 2018). Comparing index insurance based on a rainfall index and an evapotranspiration index, Von Negenborn et al (2018) found that the rainfall-based index underestimates the effect of weather on the risk of repaying agricultural credit, especially during harvest months.…”
Section: Product Qualitymentioning
confidence: 99%
“…In the current dominant narrative amongst climate policy and climate researchers, risk is characterized as resulting from a combination of hazardous events (often extreme events such as storms, floods, extreme heat), exposure of physical assets such as infrastructure, and vulnerability of human systems [15][16][17][18]. The way in which climate risk is described through the Intergovernmental Panel on Climate Change (IPCC) reports has, however, varied over time.…”
Section: Concept Of Risk Affects Approaches To Adaptationmentioning
confidence: 99%
“…Careful design of the index can help to calibrate payments to potential losses. Technological innovation, in particular the use of remote sensing, has potential to provide geographically detailed information in the absence of weather stations (Hochrainer-Stigler et al, 2014).…”
Section: Financial Protection Against Climate Risks For the Private Smentioning
confidence: 99%